Therapeutic Potential of Selected Varieties of Phoenix Dactylifera L. Against Microbial Biofilm and Free Radical Damage to DNA - Nimra Qasim; Muhammad Shahid; Fatima Yousaf; Muhammad Riaz; Fozia Anjum; Muhammad Adeel Faryad; Remsha Shabbir (SAGE Publishing, 2020)
Phoenix dactylifera L. (Date palm) is the most widely consumed fruit around the world and is rich source of nutrients containing dietary fibers, minerals, vitamins, sugar, protein and antioxidants with potent bioactivities against various microbial pathogens. This study evaluated the therapeutic potential of 2 varieties of ethanolic extracts of Phoenix dactylifera i-e Ajwa and Khalas against bacterial biofilms. This study also investigated the protective effect of Ajwa and Khalas against hydroxyl radical damage to calf thymus DNA. Antioxidant potential through different antioxidant assays showed that Ajwa has higher antioxidant potential than Khalas. Both Ajwa and Khalas presented good antimicrobial activities against Bacillus subtili s and Pasteurella multocida . Biofilm inhibition assay showed that increasing concentration of Ajwa and Khalas exhibited higher percentage of bacterial biofilm inhibition. Microscopic examination revealed significant inhibition of microbial biofilm. Ajwa and Khalas protected the calf thymus DNA against damage caused by hydroxyl radicals produced by fenton reagent. Fourier Transform Infrared (FTIR) spectra confirmed the presence of O-H, C=C and C-O functional groups in tested extracts. The study concluded that tested varieties of Date palm have the potential to inhibit bacterial biofilms and can be used for therapeutic purposes against biofilm producing pathogens.